Analisis Kestabilan Lereng Lowwall Pit X Di PT. Berkat Anugerah Sejahtera (BAS): Kestabilan Lereng Lowwall - -, lisa haryani; Djayus, Djayus; Supriyanto, Supriyanto (GEOSAINS KUTAI BASIN, 2024)
This research aims to determine the optimal value of the mine Lowwall wall safety factor and analyze the slope stability of the mine Lowwall wall. The data used in this research are slope geometry data, physical properties, rock mechanics, and geotechnical drilling data. Safety factor analysis used GLE/Morgenstern-Price method and it was found that the lowwall slope safety factor result was 1,191, higher than the minimum limit set, namely 1.1. The research results show that the slope is in a safe and stable condition so it is safe for mining, in accordance with applicable safety standards.